2013
DOI: 10.1016/j.ejogrb.2013.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Antihistamines and other prognostic factors for adverse outcome in hyperemesis gravidarum

Abstract: Objective The purpose of this study is to determine the frequency of adverse perinatal outcome in women with hyperemesis gravidarum and identify prognostic factors. Study design This is a case-control study in which outcomes of first pregnancies were compared between 254 women with hyperemesis gravidarum treated with intravenous fluids and 308 controls. Prognostic factors were identified by comparing the clinical profile of patients with hyperemesis gravidarum with a normal and an adverse pregnancy outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 20 publications
(23 reference statements)
0
27
2
1
Order By: Relevance
“…Our data suggest that overweight and obese women are more likely to experience SWL. HG has repeatedly been associated with a modest decrease in birthweight . In our study, birthweight was not clearly reduced among children born to women with SWL.…”
Section: Discussioncontrasting
confidence: 66%
“…Our data suggest that overweight and obese women are more likely to experience SWL. HG has repeatedly been associated with a modest decrease in birthweight . In our study, birthweight was not clearly reduced among children born to women with SWL.…”
Section: Discussioncontrasting
confidence: 66%
“…There is conflicting evidence on how HG may directly affect the health of the unborn child in terms of birthweight or being small‐for‐gestational‐age. Although some studies suggest that HG is not associated with adverse pregnancy outcomes, others have found associations with preterm birth and lower birthweight . Moreover, little evidence has been reported on the occurrence of stillbirth and need for neonatal care for babies born to women affected by HG.…”
mentioning
confidence: 99%
“…Interestingly, the only factor significantly linked to neurode-274 velopmental delay is early onset of symptoms, which was also 275 found in a previous study to be linked to adverse fetal outcome 276 [40]. It can be of some comfort for women to know that while 277 antihistamines, which are commonly used to treat HG, were linked 278 to preterm birth in HG pregnancies, there was no evidence of 279 antihistamine exposure being linked to neurodevelopmental delay 280 in children [40]. Consistent with our findings, in a recent study, 281…”
mentioning
confidence: 60%
“…This 229 theory is supported by rodent studies that show maternal care in 230 the first week after birth results in epigenetic modification of genes 231 expressed in the brain that shape neuroendocrine and behavioral 232 stress responsivity throughout life [28]. Interestingly, the only factor significantly linked to neurode-274 velopmental delay is early onset of symptoms, which was also 275 found in a previous study to be linked to adverse fetal outcome 276 [40]. It can be of some comfort for women to know that while 277 antihistamines, which are commonly used to treat HG, were linked 278 to preterm birth in HG pregnancies, there was no evidence of 279 antihistamine exposure being linked to neurodevelopmental delay 280 in children [40].…”
mentioning
confidence: 80%
See 1 more Smart Citation